Rare homozygous CNPY3 variant causing autosomal recessive developmental and epileptic encephalopathy 60: A case report - Nohela Rehman; Zohra Hasan Ali; Mahrukh Nasir; Salman Kirmani (Rare)
Introduction: Epilepsy is one of the most common neurological disorders, affecting around 50 million people globally. Developmental and epileptic encephalopathy 60 (DEE60) is an autosomal recessive disorder caused by mutations in the Canopy FGF signaling regulator 3 (CNPY3) gene. Symptoms start in infancy and include developmental delay, seizures, and myoclonus, with EEGs showing hypsarrhythmia indicative of West syndrome. CNPY3 is crucial for Toll-like receptor chaperoning and can potentially cause neuronal circuit imbalances. This report examines the first reported instance of DEE60 in Pakistan with a missense mutation in the CNPY3 gene, aiming to advance the current literature on CNPY3 and bring attention to a rare condition that currently only has symptomatic treatment. Only five cases have been reported globally. Methodology: Informed consent was obtained from the patient’s parents for the publication of this study and patient confidentiality has been maintained such that no data in the submission can reveal the patient's identity. Case presentation: A 5-month-old male, born of consanguineous parents, presented to the Aga Khan University Hospital with severe seizures, a history of global developmental delay and a family history of seizures. The patient had his first seizure at 3 months and was started on antiseizure medications. He was born full-term via caesarean section, requiring oxygen support postnatally due to delayed cry and cyanosis. He exhibited delayed developmental milestones, low interaction levels, unresponsiveness to loud sounds and no smiling since birth. Systemic examinations were normal, but MRI and EEG findings suggested West Syndrome, DEE, and inborn errors of metabolism (IEM). Whole exome sequencing (WES) revealed a homozygous likely pathogenic variant in the CNPY3 gene (NM_006586.5) c.275 C>T (p.Ser92Leu, rs556172653), confirming DEE60. At follow-up, the patient experienced increased seizure frequency, intermittent fever, recurrent chest infections and decreased muscle tone. Management included anti-seizure medications, benzodiazepines, anticonvulsants, neurobiotin, folic acid, vitamin B and ACTH. The parents were counselled about DEE60, prenatal testing, and a 25 % occurrence of recessive disorders. There is currently no gene therapy for this condition. Comment: The variant reported in dataebases is predicted to be deleterious, consistent with the phenotype observed in our patient. ClinVar records 34 CNPY3 variants with 20 variants of uncertain significance. This highlights the need for further research to understand CNPY3-associated phenotypes and its role in neuronal activity. Improved newborn and genetic testing access in Pakistan is essential for timely diagnosis and management, given the high costs of foreign labs and the risk of undiagnosed cases.